Flea's best friend - Fuge, Charles (Milwaukee : Gareth Stevens Pub., 1995)
When Flea sets out to find a home of his own, he tries many different kinds of dogs before he finds just the right one.
8 11 13 23 29 31 34 39
Keywords: Fleas -- Fiction; Dogs -- Fiction